2010
DOI: 10.1073/pnas.0914457107
|View full text |Cite|
|
Sign up to set email alerts
|

Surface residues dynamically organize water bridges to enhance electron transfer between proteins

Abstract: 15 ps −1 and a bath temperature of 298 K were used to propagate the equations of motion within the Langevin approach. Periodic boundary conditions were applied to simulate a continuous medium." should instead appear as "A friction coefficient of 10 ps −1 and a bath temperature of 298 K were used to propagate the equations of motion within the Langevin approach. No boundary conditions were imposed; the system freely evolved in vacuum."These errors do not affect the conclusions of the article.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(64 citation statements)
references
References 43 publications
3
61
0
Order By: Relevance
“…The first point concerns the active role played by FAD intrinsic dynamics which shows that high coupling structures are obtained due to FAD movement and presence of water molecules that bridge the ET path between both domains (FBD and GD). The key role of structural bridging waters for FHb ET paths is consistent with previous results reported by several groups who showed that water molecules are able to adapt protein contact surfaces of ET transfer complexes significantly enhancing the corresponding rate [62,[69][70][71][72][73]. Other relevant point concerns the electron entry point on the GD.…”
Section: Electron Transfer Pathwayssupporting
confidence: 87%
See 1 more Smart Citation
“…The first point concerns the active role played by FAD intrinsic dynamics which shows that high coupling structures are obtained due to FAD movement and presence of water molecules that bridge the ET path between both domains (FBD and GD). The key role of structural bridging waters for FHb ET paths is consistent with previous results reported by several groups who showed that water molecules are able to adapt protein contact surfaces of ET transfer complexes significantly enhancing the corresponding rate [62,[69][70][71][72][73]. Other relevant point concerns the electron entry point on the GD.…”
Section: Electron Transfer Pathwayssupporting
confidence: 87%
“…The computed H AB values should be considered only as an estimation of the real coupling values, but, as shown in previous works from our group [60,61] and others [58,59,62,[69][70][71][72][73], are accurate enough to distinguish and characterize different possible ET paths in the same protein, and/or preferred ET conformations, in remarkable consistency with experimental measurements of the ET rates [58,59,62,[69][70][71][72][73]. Moreover, since in the present case donor and acceptor states are the same for all studied cases, since we are dealing with the same protein, the other factors governing ET, like the reorganization energy, and ET reaction free energy, remain constant.…”
Section: Electron Transfer Pathwaysmentioning
confidence: 97%
“…The peptide backbone may mediate charge movement along the PPII helix or even allow transient localization, and explicitly including these effects could lead to higher predicted transfer rates. Furthermore, it has been shown that bridging water molecules can serve to enhance electron transfer pathways in proteins, 142,143 and a similar effect seems to be important in solvated peptides. This effect is already present in our results, seen in the importance of considering water molecules in the couplings in Table 4.…”
Section: ■ Discussionmentioning
confidence: 99%
“…de la Lande et al reported an investigation of the tunneling pathways between a quinol cofactor of the protein MADH (methylamine dehydrogenase) and a blue copper center contained in amicyanin [176]. The results from MD simulation coupled to PM analyses indicated that the protein interface favors the establishment of efficient water mediated ET pathways between the proteins.…”
Section: Water Mediated Electron Transfersmentioning
confidence: 94%